CORRECTED CALCULATION OF HORIZONTAL GATING SYSTEMS - I. A. Zayatz; V. A. Skvortsov (Литьë и металлургия, 2014)
In the course of fulfillment of work the specified calculations of horizontal gating systems for various parts produced in dispensable molds were carried out. The results of work showed that the weight removal value in gating systems fluctuates in big intervals and the specified calculation of horizontal gating systems enables to calculate precisely their weight that allows to calculate quantity of metal in metal charge.